PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI - A Charmiati, Putu Gita Hapsari; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2019)
The purpose of this study was to determine the effect of job satisfaction on Organizational Citizenship Behavior with Organizational Commitment as Variable Mediation At PT. BPR Bali Dananiaga. Organizational Citizenship Behavior is a behavior in an organization that is not directly appreciated by a formal reward system. Organizations need to pay attention to the factors that affect the Organizational Citizenship Behavior. Samples taken as many as 45 respondents. Sampling in this research using saturated sampling technique. The data was collected by distributing questionnaires using a 5-point likert scale to measure 17 statement items. The analysis technique used is Path Analysis. The result of the analysis shows that job satisfaction has positive effect on organizational commitment, job satisfaction has positive effect on organizational citizenship behavior, organizational commitment has positive effect on organizational citizenship behavior and organizational commitment acts as mediation on the influence of job satisfaction toward organizational citizenship behavior at PT. BPR Bali Dananiaga. Keywords : job satisfaction, organizational citizenship behavior, and organizational commitment